Extrinsic and intrinsic motivational factors influencing work performance of employees at the Zimbabwe National Water Authority (ZINWA). - Mandondo, Takunda Michael (Midlands State University, 2017)
The achieved purpose of the study was to determine the motivational factors influencing employee performance at ZINWA and examine how managers can utilize these motivational factors to improve employee performance. Performance levels were dropping as discontentment with the organization`s management style was intensifying. Employees had reached a point where they were just coming to work but with no definite goals and zeal to perform their tasks. The researcher then took a quantitative approach and made use of a descriptive research design in a bid to answer questions on the status quo of motivation on work performance. A target population of the office personnel at Mazowe Catchment in Harare provided a sample of 59 participants which determined by using simple random sampling through Krejcie & Morgan`s psychological measurement. The data using questionnaires was then analyzed using the Statisctical Package for Social Scientist and the presented in the form of tables and graphs indicating descriptive frequencies and percentages as well as through correlations. The research discovered that neglecting extrinsic motivational factors especially those that are part of both the employment contract and the psychological contract has the capacity diminish intrinsic motivational factors and where both factors are silent, performance compromised. The overall view of the research is that motivation is a dominant concept within the workplace and there is a need of bringing innovation and creativity to the institutionalization of motivational factors.